PENGENALAN PENTINGNYA KOPERASI PROPERTY SYARIAH DI DESA NAMBO GREEN VILLAGE - Azizah Mursyidah (Lembaga Penelitan dan Pengabdian Masyarakat Institut Agama Islam Sahid, 2023)
Sharia cooperatives are micro-institutions that adhere to sharia principles, the purpose of having sharia property cooperatives is to prepare housing based on sharia principles, namely the principle of prioritizing the element of justice, not prioritizing the principles of riba, maysir, gharar, tadlis, and zolim. This research is a study that discusses qualitative descriptive analysis and field surveys; the result of this research is increasing public understanding of sharia cooperatives connecting sharia cooperatives, as well as sharia muamalah contracts that exist in sharia cooperatives; including: ba'I Assalam, Murabahah, Ba'I Istishna, and Ijarah Muntakiya Bittamlik. and the prohibition of MAGRIB (Maysir, Gharar, Riba, Tadlis, Bathil).